Reliability analysis of ground movement in tunnelling in spatially variable soil using equivalent parameters - Yang, Wenyu; Liu, Hui; Zheng, Junjie; Cui, Lan (Frontiers in Earth Science, 2022)
The evaluation of the ground movement induced by tunnelling is of vital importance for the tunnel construction and the safety of the adjacent facilities. As the spatial variability of soil was widely acknowledged, more and more researches take insight into the uncertainty analysis for tunnelling. However, reliability analysis considering the spatial variability of soil is still a tough task since the accurate failure probability generally needs time-consuming calculation of random finite element/difference. Instead of conducting the direct Monte-Carlo simulation, this study utilizes a simplified framework to analyze the reliability of the ground movement of tunnelling. The main concept of this framework is adopting random variable model with equivalent parameters by producing the comparable failure probability as the results of random field model. Coupling with the variance reduction technique, the reliability analysis of tunnel ground movement considering more than one spatial variable can be addressed. Two tunnel cases are studied to explain the adaptability and accuracy of this simplified framework in tunnelling. The characteristic of the spatially variable soil is thoroughly comprehended through various parametric study, based on the robustness of the simplified framework. Results show that the simplified framework precisely predicts the tunnel reliability considering spatially variable soils in a relatively efficient manner.